Study on the Digital Machining Technology of Spiral Bevel Gear based on Network - Li Jubo; Li Genggeng; Jiang Chuang; Xu Kai; Zhang Hua; Li Tianxing (Jixie chuandong)
To solve the problem of single machine digital machining for spiral bevel gear,a digital machining scheme of spiral bevel gear based on network is proposed.The communication control model of the digital machining of spiral bevel gear is built,the communication control software is developed,and the network communication architecture of digital machining of spiral bevel gear is set up.Finally,the feasibility and practicability of the proposed machining scheme are proved by the digital machining application test based on network of one hypoid gear.